2019
DOI: 10.3390/fib7100092
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Injection Molded Wood-Polypropylene Composites against Basidiomycetes According to EN 15534-1: New Insights on the Test Procedure, Structural Alterations, and Impact of Wood Source

Abstract: In this study, we investigated injection molded wood-polypropylene composites based on various wood sources and their decay resistance against white rot (Trametes versicolor) and brown rot (Coniophora puteana) in a laboratory test according to EN 15534-1:2014. The manufactured composites consisted of poplar (Populus spp.), willow (Salix spp.), European beech (Fagus sylvatica L.), Norway spruce (Picea abies (L.) H. Karst.), and a commercial wood source (Arbocel® C100), respectively. All formulations were compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
3
1
0
Order By: Relevance
“…The following observations made for WPC variant I-1 were confirmed for all other tested WPC materials: Increased moisture after water storage affected MOR and MOE considerably more than fungal attacks. This finding is in line with previous studies [ 15 , 18 , 19 , 20 , 21 ]. Natural pre-weathering of the test specimens did not result in an increased reduction of MOR and MOE.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The following observations made for WPC variant I-1 were confirmed for all other tested WPC materials: Increased moisture after water storage affected MOR and MOE considerably more than fungal attacks. This finding is in line with previous studies [ 15 , 18 , 19 , 20 , 21 ]. Natural pre-weathering of the test specimens did not result in an increased reduction of MOR and MOE.…”
Section: Resultssupporting
confidence: 94%
“…Increased moisture after water storage affected MOR and MOE considerably more than fungal attacks. This finding is in line with previous studies [ 15 , 18 , 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Krause et al (2019) in their work presented the influence of various types of fungi on the structure and properties of WPCs. They showed that the moisture content of the sample plays a key role in the degradation process [ 22 ].…”
Section: Introductionmentioning
confidence: 99%